Pengaruh Kualitas Aktiva Produktif Dan Kredit Bermasalah Terhadap Profitabilitas PT. Bank Tabungan Pensiunan Nasional, Tbk - Eman, Gabriela Mike Ineke (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstracts: This study aims to analyze the influence and relationship Assets Quality and Profitability NPL against PT. National Savings Bank (BTPN), Tbk Quarter Year during the period 2010-2012. NPL is the amount of credit that are not collectible in the classification of loans classified as substandard, doubtful and loss, penilaianya by using the ratio of non-performing loans (NPL). Both of these variables is a key indicator of PT. BTPN, Tbk in gaining profit. Profitability can be measured by using the ratio of Return on Assets (ROA). In penilaianya KAP and NPL showed that the lower the company's financial performance is getting better and the effect on Increased ROA, ROA ratio the higher the value the more profitable the company. The results of the data analysis show the value of the firm and NPL PT. BTPN, Tbk is able to be compressed quite low in accordance with the provisions stipulated by Bank Indonesia (BI), KAP and NPL PT. BTPN, Tbk capable suppressed resulting in increased company profits. Test Results of Multiple Regression Statistics show that the simultaneous Assets Quality and Non Performing Loans (NPL) have a significant effect on the profitability (ROA), amounting to 90.5% Profitability is affected by the variables studied and the remaining 9.5% is influenced by variables that are not diteleti. Partial regression test results showed NPL effect on ROA of 1.46%, while the firm is very strong in the amount of 89.04% on ROA. If the variable KAP and NPL bernilan 0% (zero) then the variable ROA is worth 6%, every 1% decrease in NPL variable will increase ROA of 0.62% and each 1% decrease in KAP variables will increase by 1.235% ROA. Overall the results of the data analysis in this study PT. BTPN, Tbk showed positive financial performance and profitable. Â Keywords: earning assets, non-performing loans, return on assets